2018
DOI: 10.1002/ptr.6222
|View full text |Cite
|
Sign up to set email alerts
|

Histone acetylation increases in response to ferulic, gallic, and sinapic acids acting synergistically in vitro to inhibit Candida albicans yeast‐to‐hyphae transition

Abstract: Novel treatments are needed to prevent candidiasis/candidemia infection due to the emergence of Candida species resistant to current antifungals. Considering the yeastto-hyphae switch is a critical factor to Candida albicans virulence, phenols common in plant sources have been reported to demonstrating their ability to prevent dimorphism. Therefore, phenols present in many agricultural waste stress (ferulic (FA) and gallic (GA) acid) were initially screened in isolation for their yeast-to-hyphae inhibitory pro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
3
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 36 publications
(46 reference statements)
1
3
0
Order By: Relevance
“…According to the literature, glucosinolates decrease the microbial growth of fungi (Calmes et al 2015). The phenolic derivatives sinapine and sinapic acid are capable of reducing yeast growth (Câmara et al 2019). Similar reduction of yeast growth has been noticed for tannins (Ishida et al 2006).…”
Section: Resultssupporting
confidence: 58%
“…According to the literature, glucosinolates decrease the microbial growth of fungi (Calmes et al 2015). The phenolic derivatives sinapine and sinapic acid are capable of reducing yeast growth (Câmara et al 2019). Similar reduction of yeast growth has been noticed for tannins (Ishida et al 2006).…”
Section: Resultssupporting
confidence: 58%
“…Gallic acid had great inhibitory action against C. glabrata and C. krusei (Table 1), but better antibiofilm activity against C. krusei (Table 5). Previous studies have shown antifungal activity for gallic acid against C. albicans and filamentous fungi [33,34,35,36]; however, its activity against Candida biofilms has been poorly investigated. This compound can inhibit biofilm formation [34], as confirmed by the C. krusei antibiofilm result (MBIC) recorded here.…”
Section: Discussionmentioning
confidence: 99%
“…However, the yeast-to-hyphae transition could be disrupted by plant phenolics, such as ferulic acid 41 . These phenolics, which are the building blocks of lignin, are induced during infection 42 .…”
Section: Discussionmentioning
confidence: 99%